(untitled) (Eurasian Research Bulletin, 2022)
There are a fair number of options for the detrimental effect of coronavirus infection on the liver. It is no secret that SARS-CoV-2 exploits angiotensin-converting enzyme 2 (ACE-2) into receptor hypostases for penetration into the intracellular environment. It has been revealed that ACE-2 is more expressed on cholangiocytes, which makes the liver a possible object for the virus. Liver biopsy in patients with SARS-CoV in 2002 indicated a large increase in mitotic cells with eosinophilic bodies and balloon-like hepatocytes, suggesting that SARS-CoV may cause hepatocyte apoptosis and cause liver damage. Many studies have presented that SARS-CoV via a specific protein 7a can induce apoptosis in the subcellularlevels of various organs (including the lungs, kidneys and liver) in a caspase-dependent way, proving the possibility that SARSCoV can directly First of all, at the early stage of SARS-CoV infection , abnormal serum thresholds of cytokines and chemokines were found in patients: serum IL-1, IL-6 and IL-10 levels in patients with chronic diffuse liver disease were higher than in patients with normal or slightly reduced liver function, calculating an acceptable correlation between liver damage and inflammatory responses caused by coronavirus infection. In addition, patients with SARS with HBV/HCV infection were more resistant to altered liver damage and severe hepatitis usually are associated with increased replication of the hepatitis virus during SARS-CoV infection. Although no equal information on SARS-CoV-2 has been achieved, chronic viral hepatitis probably does not increase the likelihood of a severe prognosis for COVID-19. HBV, which is more common in China than in Europe, does not appear to affect the outcome of COVID-19. Based on this , there is no credible argument for suggesting this, immunosuppression may even provide a kind of comprehensive safety from immunopathological diseases. Processes that contribute to lung damage in cases with more dangerous expressions of the disease. Most likely this is due to the syndrome of activation of macrophages in the pro inflammatory syndrome, which qualifies as cytokine storm and multiple organ failure. Systemic viral infections are partly combined with transient increases in transaminases, which can display allthe overall immune activation or inflammation caused by circulating cytokines without impairing liver function, the socalled phenomenon of "bystander hepatitis" - hepatitis, not participating in the process. Liver damage in Covid-19 occurs entirely due to hypoxia (oxygen depletion) that develops against the background of pulmonary insufficiency. Hypoxemia that occurs with aggravated pneumonia causes ischemic liver damage in patients with coronavirus infection. A decrease in the oxygen content in the body in hypoxic conditions can lead to the death of liver cells.